2022
DOI: 10.1007/s00431-022-04579-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of early empiric antibiotics and necrotizing enterocolitis and late-onset sepsis in preterm infants: a multicenter cohort study

Abstract: The threshold to initiate empiric antibiotics for suspicion of early-onset sepsis (EOS) is low in preterm infants. Antibiotics’ effects on short-term outcomes have recently been debated. We aimed at exploring the extent of early empiric antibiotic exposure (EEAE) in preterm infants and the association between the duration of EEAE with necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) within different EEAE groups. EEAE practice for suspicion of EOS was evaluated in all included infants (gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The authors found that limited early antibiotics (≤3 days) was associated with a reduction in NEC compared to untreated controls (0.74, 95% CI 0.55–0.99); but prolonged early antibiotics (>3 days) was not associated with either increased or decreased NEC risk when compared to either 0 days or ≤3 days. Dierikx et al ( 23 ) also performed additional analysis based on duration of treatment and found similar results of protective effects of limited early antibiotics given for ≤3 days; whereas prolonged early antibiotics (>3 days) was neither harmful nor protective. While these two studies suggest that a limited course of early antibiotics (≤3 days) may help reduce the risk for NEC in preterm infants, the study by Vatne et al ( 34 ) had different results.…”
Section: Human Studies Of Early Antibiotics and Necmentioning
confidence: 75%
See 3 more Smart Citations
“…The authors found that limited early antibiotics (≤3 days) was associated with a reduction in NEC compared to untreated controls (0.74, 95% CI 0.55–0.99); but prolonged early antibiotics (>3 days) was not associated with either increased or decreased NEC risk when compared to either 0 days or ≤3 days. Dierikx et al ( 23 ) also performed additional analysis based on duration of treatment and found similar results of protective effects of limited early antibiotics given for ≤3 days; whereas prolonged early antibiotics (>3 days) was neither harmful nor protective. While these two studies suggest that a limited course of early antibiotics (≤3 days) may help reduce the risk for NEC in preterm infants, the study by Vatne et al ( 34 ) had different results.…”
Section: Human Studies Of Early Antibiotics and Necmentioning
confidence: 75%
“…Using prospective data collected from 13 neonatal intensive care units from five continents, Li et al found that NEC incidence was lower among infants treated with early antibiotics compared to infants with no antibiotic exposure (aOR 0.25, 95% CI 0.12-0.47). Lastly, Dierikx et al (23) studied 1,259 very low birth weight (VLBW) infants from 9 centers in the Netherlands and Belgium and found that early antibiotics was associated with decreased risk for NEC compared to no antibiotics (aOR 0.47, 95% CI 0.23-0.96). Analysis based on duration of treatment provided additional insights regarding the relationship between early antibiotics and NEC.…”
Section: First Author and Year Sample Size Intervention Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subgroup analysis including only the studies by Boo and Cheah and Reed et al shows no association of MAB with NEC. The effect of antibiotics given shortly before birth can be overshadowed by confounding factors, such as being born by cesarean section, feeding methods, or probiotic supplementation ( 58 ). In the two studies reporting on this, the use of cesarean sections was higher in the control group.…”
Section: Discussionmentioning
confidence: 99%